2021
DOI: 10.3389/fcell.2021.745394
|View full text |Cite
|
Sign up to set email alerts
|

Stress Granules Involved in Formation, Progression and Metastasis of Cancer: A Scoping Review

Abstract: The assembly of stress granules (SGs) is a well-known cellular strategy for reducing stress-related damage and promoting cell survival. SGs have become important players in human health, in addition to their fundamental role in the stress response. The critical role of SGs in cancer cells in formation, progression, and metastasis makes sense. Recent researchers have found that several SG components play a role in tumorigenesis and cancer metastasis via tumor-associated signaling pathways and other mechanisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 158 publications
(214 reference statements)
0
16
0
Order By: Relevance
“…Y-box-binding protein 1 (YBX1) is a multifunctional transcription/translation factor that can bind to a target promoter or enhancer through the Y-box motif, a CCAAT box (or an ATTGG inverted box) ( 25 , 27 , 28 ). A series of downstream target genes of YBX1 are oncogenes that are involved in malignant growth, chemoresistance, metastasis, tumor angiogenesis, and stem-like properties ( 24 , 29 32 ). Moreover, we found that high YBX1 expression in lung adenocarcinoma is associated with poor prognosis and metastasis in patients ( 33 , 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Y-box-binding protein 1 (YBX1) is a multifunctional transcription/translation factor that can bind to a target promoter or enhancer through the Y-box motif, a CCAAT box (or an ATTGG inverted box) ( 25 , 27 , 28 ). A series of downstream target genes of YBX1 are oncogenes that are involved in malignant growth, chemoresistance, metastasis, tumor angiogenesis, and stem-like properties ( 24 , 29 32 ). Moreover, we found that high YBX1 expression in lung adenocarcinoma is associated with poor prognosis and metastasis in patients ( 33 , 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TIA1 can directly mediate the translational silencing and turnover of ARE-containing mRNAs and non-coding RNAs (ncRNAs) and can indirectly function as a molecular sponge to modulate the regulatory activity mediated by microRNAs [ 9 , 10 , 11 , 15 , 16 , 17 , 18 , 19 , 20 ]. Given the presence of TIA1 and other RBPs that determine the fate of many cellular RNAs in SGs, these foci function as dynamic sites of RNA triage during stress, where molecular decisions are made regarding the composition of RNA ribonucleoprotein complexes and their subsequent engagement with the translation or degradation machinery by modulating the cellular and metabolism fate with pathophysiological consequences on normal and abnormal cell growth [ 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological importance of SGs and their RNP components in the formation, progression and metastatic fate of several human solid tumors have been recently reported and reviewed [ 133 , 134 ]. It is known that genome integrity must be tightly preserved to ensure cellular survival and to deter the genesis of disease.…”
Section: Phylogenetics and Cellular/tissular Expression Profilingmentioning
confidence: 99%